Roughness of (ℤ+,ℤ-)-Nonuniform Exponential Dichotomy for Difference Equations in Banach Spaces - Nicolae Lupa (The Scientific World Journal)
In this paper we study the roughness of (ℤ+,ℤ-)-nonuniform exponential dichotomy for nonautonomous difference equations in the general context of infinite-dimensional spaces. An explicit form is given for each of the dichotomy constants of the perturbed equation in terms of the original ones. We emphasize that we do not assume any boundedness condition on the coefficients.